PRINSIP ANDRAGOGI PADA PERFORMASI TUTOR PROGRAM PENDIDIKAN LUAR SEKOLAH - Lilis Karwati (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2017)
Adult Education is a process where people who already have a social role as adult learning activities are continuous and systematic with the aim to make the changes in knowledge, attitudes, values, and skills, so that in the process of teaching should be done through the implementation of Andragogy learning methods so that tutors in conducting educational programs in the field of School accordance with prinsiporangdewasa approach so that the goal of building human and nation building can be achieved. various policies set by the government, but on the field, not a few adults who have to get out of school education, for example in the form of skills training, courses, upgrading and so forth. To membelajarkan adults through adult education can be done by various methods and strategies needed. In this case, the adult learning has a maturity of self-concept moves from dependency as occurs in childhood toward independence or self-direction.Keywords: Andragogi, Tutor Performance.